2003
DOI: 10.1111/j.1574-6941.2003.tb01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of the herbicide trifluralin by bacteria isolated from soil

Abstract: Trifluralin (alpha,alpha,alpha-trifluoro-2,6-dinitro-N,N-dipropyl-p-toluidine; TFL) is a pre-emergence, soil-incorporated herbicide that has been in agricultural use since the early 1960s and is moderately persistent in soil. The purpose of this study was to isolate and characterise TFL-resistant bacteria from a soil in which this pesticide has been used for the last four decades and to determine their ability to degrade TFL using HPLC. Eight bacteria were isolated by repeated subculture in liquid medium with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 18 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…Hence, microorganisms that have developed resistance to pesticides are capable of frequently degrading them (Curutiu et al, 2017). Resistance against pesticides in general is attributed due to physiological changes that induce microbial metabolism to follow a new metabolic pathway that help organisms to bypass a biochemical reaction which could otherwise be inhibited by some specific pesticides (Bellinaso et al, 2003). Also, the resistance could be due to emergence of mutations inherited by successors of microbes (Herman et al, 2005).…”
Section: Characterization and Identification Of Herbicide Tolerant Rhmentioning
confidence: 99%
“…Hence, microorganisms that have developed resistance to pesticides are capable of frequently degrading them (Curutiu et al, 2017). Resistance against pesticides in general is attributed due to physiological changes that induce microbial metabolism to follow a new metabolic pathway that help organisms to bypass a biochemical reaction which could otherwise be inhibited by some specific pesticides (Bellinaso et al, 2003). Also, the resistance could be due to emergence of mutations inherited by successors of microbes (Herman et al, 2005).…”
Section: Characterization and Identification Of Herbicide Tolerant Rhmentioning
confidence: 99%
“…Therefore, microbial resistance to a pesticide was linked with their capacity to degrade it (Kumar et al, 1996;Ortiz-Herna´ndez and Sa´nchez-Salinas, 2010). As reported by Bellinaso et al (2003), the resistance can be temporal or permanent, where physiological changes occur as the temporal tolerance mechanisms to alleviate the inhibitory effects of the pesticide. Permanent resistance, on the other hand, is expected as a result of genetic modifications, inherited by the subsequent generation of microbes (Herman et al, 2005;Johnsen et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The microorganism's physiology and genetic's play a key role on their tolerance or resistance to pesticides. Generally, the microorganisms resistant to pesticide have a great potential to break the pesticides into simple products, which may be used by them as nutrient sources, such as carbon and phosphorus (Cassigneul et al, 2016;Myresiotis et al, 2012;Bellinaso et al, 2003). According to the results of (Wijekoon et al, 2018) which have shown that Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 99%